2016
DOI: 10.1371/journal.pcbi.1005152
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating Emergent Transport Properties for Molecular Motor Ensembles: A Semi-analytical Approach

Abstract: Intracellular transport is an essential function in eucaryotic cells, facilitated by motor proteins—proteins converting chemical energy into kinetic energy. It is understood that motor proteins work in teams enabling unidirectional and bidirectional transport of intracellular cargo over long distances. Disruptions of the underlying transport mechanisms, often caused by mutations that alter single motor characteristics, are known to cause neurodegenerative diseases. For example, phosphorylation of kinesin motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Nevertheless, one can easily adapt our method to engineer novel heterodimers to gain new insights into the motility mechanisms and functions of different kinesins. For example, a kinesin heterodimer with two nonidentical neck linkers that differ in length and/or amino acid composition would be an extremely useful reagent for dissecting the mechanical role of the neck linker, and crippled kinesin heterodimers can be used to further understand how kinesins coordinate in multimotor ensembles to achieve optimal efficiency. Due to the advantages of a heterolinker of tunable composition and length, which is reactive toward two different ncAA-containing proteins, this method should allow exploration of a variety of engineered heteroprotein complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, one can easily adapt our method to engineer novel heterodimers to gain new insights into the motility mechanisms and functions of different kinesins. For example, a kinesin heterodimer with two nonidentical neck linkers that differ in length and/or amino acid composition would be an extremely useful reagent for dissecting the mechanical role of the neck linker, and crippled kinesin heterodimers can be used to further understand how kinesins coordinate in multimotor ensembles to achieve optimal efficiency. Due to the advantages of a heterolinker of tunable composition and length, which is reactive toward two different ncAA-containing proteins, this method should allow exploration of a variety of engineered heteroprotein complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Cytoskeletal motors link to their cellular cargoes through diverse mechanisms ranging from adaptor protein intermediates to lipid molecules that directly bind the motor. , The diversity in cargo–motor attachments translates into distinct linkage stiffness regimes in cellular membrane traffic. Both experimental and theoretical studies have shown that linkage stiffness alters motile properties, such as the velocity and run length of cytoskeletal motors. However, the mechanistic basis of these changes, in terms of stepping behavior and force generation, is not well understood and is the focus of this study.…”
mentioning
confidence: 99%
“…For instance, molecular motors can participate in cancer processes, such as a possible connection between KIF11 and prostate cancer [50], and between KIF11 and Taxol resistance [51]. Molecular motors also can participate in neurogenerative disease, such as a functional interaction between kinesin-I and amyloid precursor protein in Alzheimer's disease [52], in phosphorylation in Huntington's disease [53], and in axonal transport in Alzheimer's disease [54,55]. Metabolism is central to all cellular processes, and modifications in motors can affect dynamin and glucose uptake [56] and mitochondrial fusion and fission [57].…”
Section: Dynamical Diseasementioning
confidence: 99%